A survey on IP-based wireless sensor networks solutions - Rodrigues, Joel (2014)
Submitted by Paulo Alexandre Neves (pneves@ipcb.pt) on 2011-02-01T18:06:27Z No. of bitstreams: 1 Wiley_Storage.pdf: 320868 bytes, checksum: ce0e68ae6f1fdcc9e5a68b66f67fd670 (MD5)